AT 1 receptor blockade delays postlactational mammary gland involution: a novel role for the renin angiotensin system - Nahmod, Karen Amelia (2012)
Angiotensin II (AngII), the main effector peptide of the renin-angiotensin system (RAS), participates in multiple biological processes, including cell growth, apoptosis, and tissue remodeling. Since AngII activates, in different cell types, signal transducing pathways that are critical for mammary gland postlactational regression, we investigated the role of the RAS during this process. We found that exogenous administration of AngII in mammary glands of lactating Balb/c mice induced epithelium apoptosis [2.9±0.5% (control) vs. 9.6±1.1% (AngII); P < 0.001] and activation of the proapoptotic factor STAT3, an effect inhibited by irbesartan, an AT1 receptor blocker. Subsequently, we studied the expression kinetics of RAS components during involution. We found that angiotensin-converting enzyme (ACE) mRNA expression peaked 6 h after weaning (5.7-fold; P<0.01), while induction of angiotensinogen and AT1 and AT2 receptors expression was detected 96 h after weaning (6.2-, 10-, and 6.2-fold increase, respectively; P<0.01). To assess the role of endogenously generated AngII, mice were treated with losartan, an AT1 receptor blocker, during mammary involution. Mammary glands from losartan-treated mice showed activation of the survival factors AKT and BCL-XL, significantly lower LIF and TNF-α mRNA expression (P<0.05), reduced apoptosis [12.1±2.1% (control) vs. 4.8±0.7% (losartan); P<0.001] and shedding of epithelial cells, inhibition of MMP-9 activity in a dose-dependent manner (80%; P<0.05; with losartan IC50 value of 6.9 mg/kg/d] and lower collagen deposition and adipocyte invasion causing a delayed involution compared to vehicle-treated mice. Furthermore, mammary glands of forced weaned AT1A- and/or AT1B-deficient mice exhibited retarded apoptosis of epithelial cells [6.3±0.95% (WT) vs. 3.3±0.56% (AT1A/AT1B DKO); P<0.05] with remarkable delayed postlactational regression compared to wild-type animals. Taken together, these results strongly suggest that AngII, via the AT1 receptor, plays a major role in mouse mammary gland involution identifying a novel role for the RAS.